Implementasi Program E-Government Sirancak dalam Meningkatkan Pelayanan di Dinas Kependudukan dan Pencatatan Sipil Kota Padang - Qibty Veronica Rahma; Dina Atika Hesti; Vira Astuti; Ahmad dhany; Rahmadhona Fitri Helmi (Lembaga Pengembangan Kinerja Dosen, 2024)
Public service is a key focus for the government in improving the quality of life of the community. The implementation of e-government is the government's effort to increase the efficiency, transparency, and accessibility of public services through the utilization of information and communication technology. The Department of Population and Civil Registration (Disdukcapil) of Padang City has implemented an online service innovation called SIRANCAK to facilitate the community in accessing population administration services. However, there are still several obstacles such as lack of socialization, uncertainty in procedures, and lack of public understanding in using the SIRANCAK online service system. This study aims to analyze the reliability, responsiveness, and assurance of the services provided by the SIRANCAK online service, as well as provide recommendations to improve the quality of public services at the Disdukcapil of Padang City.